Open science initiatives: challenges for public health promotion. - Holzmeyer, Cheryl (Health Promotion International, 2019)
While academic open access, open data and open science initiatives have proliferated in recent years, facilitating new research resources for health promotion, open initiatives are not one-size-fits-all. Health research particularly illustrates how open initiatives may serve various interests and ends. Open initiatives not only foster new pathways of research access; they also discipline research in new ways, especially when associated with new regimes of research use and peer review, while participating in innovation ecosystems that often perpetuate existing systemic biases toward commercial biomedicine. Currently, many open initiatives are more oriented toward biomedical research paradigms than paradigms associated with public health promotion, such as social determinants of health research. Moreover, open initiatives too often dovetail with, rather than challenge, neoliberal policy paradigms. Such initiatives are unlikely to transform existing health research landscapes and redress health inequities. In this context, attunement to social determinants of health research and community-based local knowledge is vital to orient open initiatives toward public health promotion and health equity. Such an approach calls for discourses, norms and innovation ecosystems that contest neoliberal policy frameworks and foster upstream interventions to promote health, beyond biomedical paradigms. This analysis highlights challenges and possibilities for leveraging open initiatives on behalf of a wider range of health research stakeholders, while emphasizing public health promotion, health equity and social justice as benchmarks of transformation.